2017
DOI: 10.1073/pnas.1614979114
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation aftereffects reveal that tactile distance is a basic somatosensory feature

Abstract: The stage at which processing of tactile distance occurs is still debated. We addressed this issue by implementing an adaptation-aftereffect paradigm with passive touch. We demonstrated the presence of a strong aftereffect, induced by the simultaneous presentation of pairs of tactile stimuli. After adaptation to two different distances, one on each hand, participants systematically perceived a subsequent stimulus delivered to the hand adapted to the smaller distance as being larger. We further investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 62 publications
8
66
0
Order By: Relevance
“…1a,b). Because low-level skin maps are thought to be anatomically organized (26), common external-spatial error across the two postures would indicate motor error of the pointing hand rather than perceptual localization error on the target arm. Participants reached, with their eyes closed, using their right index finger to the left forearm, touched down, and then moved their finger across the skin until they felt to have reached the target.…”
Section: Resultsmentioning
confidence: 99%
“…1a,b). Because low-level skin maps are thought to be anatomically organized (26), common external-spatial error across the two postures would indicate motor error of the pointing hand rather than perceptual localization error on the target arm. Participants reached, with their eyes closed, using their right index finger to the left forearm, touched down, and then moved their finger across the skin until they felt to have reached the target.…”
Section: Resultsmentioning
confidence: 99%
“…On one model, perceived distance may be a relatively direct readout of the structure of tactile 42 space as coded by body maps in early somatosensory cortex. This interpretation is supported 43 by the fact that tactile distance adaptation aftereffects show low-level characteristics such as 44 orientation-and location-specificity (Calzolari et al, 2017), as well as by the relation between 45 tactile distance illusions and factors such as cortical magnification and RF geometry. In this 46 case, the representation of the body (i.e., hand) in SI should mirror the distortions observed 47 perceptually.…”
Section: Introductionmentioning
confidence: 95%
“…Since the pioneering work of Weber (1834Weber ( /1996, the perception of tactile distance 3 has been widely used to investigate the somatosensory system and its links to higher-level 4 aspects of body representation. Recent results have shown that tactile distance is susceptible 5 to sensory adaptation (Calzolari, Azañón, Danvers, Vallar, & Longo, 2017), suggesting that it 6 might be a basic feature coded at relatively early stages of somatosensory processing. Indeed,7 there is evidence that perceived tactile distance is shaped by low-level features of 8 somatosensory organization such as cortical magnification (Cholewiak, 1999;Taylor-Clarke, 9 Jacobsen, & Haggard, 2004;Weber, 1834Weber, /1996 and receptive field (RF) geometry (Brown, 10 Fuchs, & Tapper, 1975;DiCarlo, Johnson, & Hsiao, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The stimuli were wooden sticks which tapered to a point (~1mm) but were not sharp, similar to those we have used in previous studies 13 , 16 , 19 , 29 , 63 , 64 . Pairs of sticks were mounted in foamboard, separated by 20, 30, or 40 mm.…”
Section: Experiments 1 – Forced-choice Judgmentsmentioning
confidence: 99%